FAKTOR - FAKTOR YANG BERHUBUNGAN DENGAN TINGKAT PARTISIPASI IBU DALAM PENIMBANGAN BALITA KE POSYANDU DI WILAYAH KERJA PUSKESMAS DARUSSALAM KECAMATAN MEDAN PETISAH TAHUN 2013 - S.hindu Mathi; Heru Santosa; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2013)
Abstract The scope of under-five-year-old children weighing in Integrated Health Service is one of indicator that show the high/low participation of community in Integrated Health Service. The scope of under-five-years-old children weighing is percentage of under-five-years-old children weighed in Integrated Health Service divided by the total under-five-year-old children attending Integrated Health Service. In Medan City, the participation was still classified as very low in 2011 which there were 251,199 under-five-year-old children weighed only 126,107 (50.20%). The lowest scope of under-five-year-old children weighing in Integrated Health Service was in the working area of Darussalam’s Community Health Centre Medan Petisah Subdistrict in 2011 that amounted to 35.19%. Design of this research was cross sectional with descriptive analytic type in order to know some factors which were related to mothers’ participation in weighing their babies in the Integrated Health Service’ at Darussalam’s Community Health Centre Medan Petisah subdistrict, Medan city. The population was all mother with their 241 babies in health center work Puskesmas Darussalam in 2013.The technique of sampling was simple random sampling and 78 of them were selected to be sample. Data were collected by using questionnaires. Data analysis included univariate and bivariate by using chi-square test. The results of research showed that the mothers’ participation in weighing their babies in the Integrated Health Service’ was bad ; only 39.7 percent of the participation was good. The chi-square test showed that the factors related to mothers’ participation in weighing their babies in the Integrated Health Service’ were mother’s knowledge (p=0.019), mother’s attitude (p=0.021), and in the Integrated Health Service cadre’s attitude (p=0.005). It is expected to the Medan City Health Office or Darussalam’s Community Health Centre officers to counsel mothers with under-five-year-old children to increase their knowledge about the purpose and benefits of growth monitoring and early childhood development through a child's weighing in Integrated Health Service and provide information on how to read a child's growth in Road to Health Care. It is also suggested to increase the cooperation between the cadres with the various parties, especially with community leaders, Empowerment of Family Welfare through the activities of Integrated Health Service and receive the monitoring and supervision of Darussalam’s Community Health Centre and their equipment at Integrated Health Service and encourage people to participate in the implementation of the Integrated Health service’. Keywords : Factors, Predisposing, Enabling, Reinforcing, Participation, Integrated Health Service.